ANALISIS PELAKSANAAN MANAJEMEN RISIKO DENGAN APLIKASI ENTERPRISE RISK MANAGEMENT PADA PT BUKIT ASAM TBK - Indah Zulya Astari (ABIS: Accounting and Business Information Systems Journal, 2018)
This study aims to identify and analyze the implementation of risk management usingEnterprise Risk Management (ERM) application at PT Bukit Asam, Tbk., which is indicatedas nonoptimal, This research is performed to identify the causes why the use of ERMapplication is not optimally implemented at the company, by using ISO 31000 as the studyguide. The ISO 31000 is analyzed in this research in terms of risk management processfocusing on the seven processes. The seven processes are communication and consultation,context assignment, risk identification, risk analysis, risk evaluation, risk treatment, andmonitoring and review. The research results show that the nonoptimal implementation of riskmanagement using the ERM application happens because there are several modules of ERMapplication not yet used, and because there is a lack of awareness on the importance of riskassessment in the company. These aspects should become PT Bukit Asam Tbk.’s attention inimplementing risk management with the help of ERP application.